Astrometric Positioning of Geostationary Satellites (PASAGE) - C. Abad (Revista Mexicana de Astronomía y Astrofísica, 2006)
The main lines of PASAGE Project of the Real Instituto y Observatorio de la Armada (Spain) are described.The goal of this project is to generate precise ephemeris of geostationary satellites by means of ground basedvisual astrometric observations. It would be a more precise technique than the techniques used at present andit will be a new and important application of ground based astronomy.